Empowering against poverty through basic education - Unesco (Paris : Unesco, 2000)
The basic education in Africa
Copy available in DVD format
Executive producer, Marc Gilmer ; editor, Frederic Bonnet and Sophie Lefait ; This film has been produced with the support of Foreign Affairs and TV5 Africa
Keywords: Basic education